Analisis Tokoh Utama “Sultan Haji” Pada Naskah “Surosowan Burak” karya Toto St Radik - Saiyah, siti; Permanasari, Alis Triena; Roekmana, Giri Mustika (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2022)
Characters are divided into several types, namely the main character or central character and supporting characters. Every character must have a character or character which is also called characterization. Characterization is the author's way of presenting the characters in the story so that the character or nature of the characters can be known. The research method used is descriptive qualitative research method, a research conducted through an approach that emphasizes the researcher as a key research instrument that plans, implements, collects data, draws conclusions and compiling a complete and systematic research report. There are four scenes in Toto St Radik's "Surosowan Burak" mask. Analyzed by reading the script and observing the author's description of the character's form which includes: age, gender, appearance, social and psychological conditions that make it easy for the audience to recognize the character. the author's description of the form of character which includes: physiological dimensions (physical characteristics), psychological dimensions (mental) and sociological dimensions (social).Keywords: character, characterization, physiological, psychological, sociological